2010
DOI: 10.1007/s11192-010-0235-3
|View full text |Cite
|
Sign up to set email alerts
|

Agrifood research in Europe: a global perspective

Abstract: The paper has the general aim of assessing the worldwide research activity in agricultural and food science and technology as it is reflected by the mainstream journal literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…In some studies in other fields, a trend of the total EU scientific production surpassing that of USA has been observed (Gauffriau et al 2008). EU had in total more publications than USA within the fields of aquaculture and fisheries, although USA had a higher citation rate, especially in fisheries (Borsi and Schubert 2011).…”
Section: Country Of Publicationmentioning
confidence: 98%
See 1 more Smart Citation
“…In some studies in other fields, a trend of the total EU scientific production surpassing that of USA has been observed (Gauffriau et al 2008). EU had in total more publications than USA within the fields of aquaculture and fisheries, although USA had a higher citation rate, especially in fisheries (Borsi and Schubert 2011).…”
Section: Country Of Publicationmentioning
confidence: 98%
“…Long-term continuity in research also pays off, since all of the most productive institutions have been involved in sturgeon research for the whole period examined. According to Borsi and Schubert (2011), research within aquaculture and fisheries in EU is dominated by state-owned institutions.…”
Section: Institutionsmentioning
confidence: 99%
“…The following six aspects were discussed: 1) history and current organization of the company, 2) business Publications and citation data of scientific publications in plant breeding and plant biotechnology were used to identify the international position of Dutch research in this field. Based on the search profile of Borsi and Schubert [32], publications and citation data were taken from Thomson-Reuter's Web of Science (WoS) from 1945 and onwards. The publications that were relevant for the seed business were chosen to be: plant genetics, plant molecular biology, and plant breeding.…”
Section: Methodsmentioning
confidence: 99%
“…To visualize the international position of Wageningen UR among its peers, we analysed the worldwide network of authorships of all top 1% scientific publications in plant genetics, plant molecular biology, and plant breeding [32] from 1945 to 2012 (as explained in the methodology section). We found that the percentage of top papers with an international authorship increased substantially over time, and accounts for nearly half of all contributions in the latest period (Table 5).…”
Section: International Collaboration and Excellence Of Dutch Plant Scmentioning
confidence: 99%
“…That type of assessment has been so far conducted within broader scientific fields, such as the one conducted by Neff and Corley (2009) within the general field of ecology, or within more focused areas, such as the one conducted by Azevedo et al (2010) on the freshwater ichthyology in Brazil. One recent study also focused on the research within agricultural industry and food production in Europe, including fishery and aquaculture (Borsi and Schubert, 2011), while Nikolic et al (2011) assessed research on seven diadromous fish species. Nevertheless, there have not been such studies so far conducted in the field of fisheries science.…”
Section: Introductionmentioning
confidence: 99%